Architectural Sketches and Drawings from the Empress Elizabeth Petrovna’s Trip across Ukraine (1744) in the Collection of the National Museum in Stockholm - Staniukovich-Denisova, Ekaterina Iu. (Actual Problems of Theory and History of Art, 2020)
The article provides an overview of the collection of architectural drawings from the National Museum (Stockholm) associated with the pilgrimage of the Empress Elizabeth Petrovna to Ukraine, accompanied by the court and the Grand Ducal couple (July – September 1744). The sheets depict the buildings in which the Empress and her entourage lived and visited. The body of drawings with explanatory inscriptions, which were a kind of travel notes, together with the “Journal of the Empress’s procession from Moscow to Kiev” is of great value as a historical source that gives information about the appearance of the lost buildings, and once again confirms their attribution to Friedrich Wilhelm von Bergholtz, the chief chamberlain of Grand Duke Peter Fedorovich, who accompanied him on the trip.The research was funded by Government Program of the Russian Federation “Development of science and technology” (2013–2020) within Program of Fundamental Researches of Ministry of Construction, Housing and Utilities of the Russian Federation and Russian Academy of Architecture and Construction Sciences, the theme 1.2.21.
Keywords: architecture of Ukraine; architectural drawings; Friedrich Wilhelm Bergholtz; Little Russia; Empress Elizabeth Petrovna; travel drawings; 18th century; Kiev; Baturin; pilgrimage